Mycobacterium tuberculosis ClpP proteases are co-transcribed but exhibit different substrate specificities. - Yoann Personne (Public Library of Science (PLoS), 2013)
Caseinolytic (Clp) proteases are widespread energy-dependent proteases; the functional ATP-dependent protease is comprised of multimers of proteolytic and regulatory subunits. Mycobacterium tuberculosis has two ClpP proteolytic subunits (ClpP1 and ClpP2), with both being essential for growth in vitro. ClpP1 and clpP2 are arranged in an apparent operon; we demonstrated that the two genes are co-expressed under normal growth conditions. We identified a single promoter region for the clpP1P2 operon; no promoter was detected upstream of clpP2 demonstrating that independent expression of clpP1 and clpP2 was highly unlikely. Promoter activity was not induced by heat shock or oxidative stress. We identified a regulatory region upstream of the promoter with a consensus sequence matching the ClgR regulator motif; we determined the limits of the region by mutagenesis and confirmed that positive regulation of the promoter occurs in M. tuberculosis. We developed a reporter system to monitor ClpP1 and ClpP2 enzymatic activities based on LacZ incorporating ssrAtag sequences. We showed that whilst both ClpP1 and ClpP2 degrade SsrA-tagged LacZ, ClpP2 (but not ClpP1) degrades untagged proteins. Our data suggest that the two proteolytic subunits display different substrate specificities and therefore have different, but overlapping roles in M. tuberculosis.